Mood symptoms Associated with CADASIL Syndrome: A Case Report - Asad Shaikh; Joel Idowu (CNS Spectrums, 2021)
Abstract Objective To discuss the psychiatric symptoms that are associated with CADASIL syndrome Abstract Cerebral: Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy (CADASIL) is a rare type of hereditary disease involving the small cerebral vessels. The clinical symptoms are various and include recurrent ischemic strokes, migraine with aura, seizures with epilepsy, psychiatric problems such as mood disturbances, and progressive cognitive decline leading to dementia. This disease needs awareness amongst the psychiatrists even though it is discussed much more in neurology literature. Psychiatric symptoms are seen in 20–41% of patients with CADASIL syndrome (1, 2). Psychiatric symptoms are actually the initial presentation in 15% of the cases. (3) The psychiatric disturbance most reported are mood disturbances (9–41%) especially depression. Here a 42-year-old African American female was brought to the hospital emergency room after she was found wandering in the streets. Psychiatry was consulted for altered mental status. Upon evaluation by the psychiatric consult service she was only oriented to person, depressed, anxious and complaining of headaches. Initial CT scan showed marked small vessel disease and old lacunar infarcts in the basal ganglia and right corona radiata. Magnetic Resonance Imaging (MRI) of the brain showed acute infarcts in the right posterior frontal and right parietal lobes along with old infarcts. Her symptoms and findings on imaging were consistent with CADASIL syndrome. Once the diagnosis was confirmed and prior records were obtained patient was resumed on an antidepressant and anxiolytic. Conclusion The purpose of this case report was to discuss psychiatric symptoms associated with CADASIL syndrome. Although there has been research showing a relationship between vascular disease and depression, a review of the literature suggests that there needs to be more research done to explore other psychiatric disturbances that may be seen with this syndrome. Psychiatric symptoms that are untreated can have the potential to further impact the quality of life therefore psychiatrists need to be aware of this syndrome in order to treat these patients promptly. References 1 https://bmcmedicine.biomedcentral.com/articles/10.1186/s12916-017-0778-8 2 http://dx.doi.org/10.32474/OJNBD.2018.01.000101 3 https://pdfs.semanticscholar.org/47f6/5952ee3c5dcf2a61345f704914b17fa8dc0d.pdf